Kedudukan Hukum Hubungan Kemitraan pada Platform Transportasi Digital Perusahaan Transnational Corporation dalam Perspektif Hukum Perdata Internasional: Penelitian - Exal Sinaga; Ivan Nurchalik; Bernard Sindak Pangihutan Lumban Siantar; Hammamtio; Diani Sadiawati (PT PUSTAKA CENDEKIA GROUP, 2026)
The transnational expansion of the gig economy has triggered a doctrinal conflict of characterization between private commercial contracts and the imperative of worker protection. Transnational Corporations (TNCs) systematically exploit foreign choice-of-law clauses to circumvent domestic labor jurisdictions. This doctrinal legal research employs statutory and conceptual approaches to deconstruct the contractual relationship between TNCs and gig drivers within the framework of Private International Law (PIL). The findings demonstrate that characterizing this relationship as a pure commercial partnership is legally defective due to the operational reality of algorithmic subordination. Grounded in the principle of Favor Laboratoris and aligning with global standards (ILO Convention No. 193 and the EU Platform Work Directive), this arrangement must be recharacterized as an employment relationship. Furthermore, the analysis reveals that Presidential Regulation No. 27 of 2026 doctrinally functions as overriding mandatory rules (Lois de Police). Amidst TNCs' tactics of algorithmic fee manipulation, this regulation grants national courts the absolute jurisdiction to nullify foreign arbitration provisions and cross-border choice-of-law clauses. In conclusion, the sovereignty of Indonesia’s socio-economic public policy must prioritize the primacy of facts to dismantle transnational algorithmic exploitation, thereby safeguarding the fundamental rights and legal certainty of gig workers.